Deconstructing National Food Security: A Spatial Analysis of Paddy Field Conversion and Rice Production Volatility Based on Area Frame Sampling (AFS) Data - Luh Putu Suciati; Pieter J. Kunu (CV. HEI PUBLISHING INDONESIA, 2026)
This study analyzes the structural vulnerability of national food security by examining the spatial impact of paddy field conversion on rice production volatility. Production instability is influenced by several key factors, including land-use change, climate-related harvest failures, and the degradation of primary irrigation infrastructure. Using the Area Frame Sampling (AFS) approach from 2020 to 2024, this research integrates remote sensing data with field observations to measure the loss of productive agricultural land. The results reveal a 4.22% decline in the national harvest area. In Java, the conversion of technically irrigated paddy fields leads to an estimated loss of 11.4 tons of Milled Dried Grain (MDG) per hectare annually, reflecting a significant reduction in production capacity due to the disappearance of multi-cropping systems. Spatial regression analysis shows a strong relationship (R² = 0.78) between infrastructure expansion and rice supply instability. This finding indicates that irreversible land-use change, rather than yield fluctuation, is the primary driver of production volatility. The results suggest that national food security is approaching a critical threshold. Therefore, the study recommends implementing a moratorium on paddy field conversion, strengthening field-level spatial monitoring, integrating food security policies, and providing fiscal incentives to protect remaining agricultural land.